Role of Glutamate Autoreceptors at Hippocampal Mossy Fiber Synapses - Kwon, Hyung-Bae (Neuron, 2008)
Presynaptic autoreceptors modulate transmitter release at many synapses. At the mossy fiber to CA3 pyramidal cell (mf-CA3) synapse, two types of glutamatergic autoreceptors have been identified; transmitter release is reportedly suppressed by metabotropic glutamate receptors (mGluRs) and augmented by kainate receptors (KARs). However, the net effect of these autoreceptors when activated by endogenous glutamate is unknown. Here, we show that during low-frequency mossy fiber stimulation, glutamate acting through presynaptic mGluRs substantially suppresses transmitter release. However, using similar recording conditions, we find that presynaptic KARs are insufficient to facilitate transmitter release over a wide range of mossy fiber stimulus frequencies, indicating that the uniquely robust mf-CA3 short-term plasticity is KAR-independent. Furthermore, we report that actions generally attributed to presynaptic KARs are likely due to activation of recurrent CA3 network activity. Thus, negative feedback via presynaptic mGluRs is the dominant mode of glutamatergic autoregulation at the mf-CA3 synapse.